Advances in Knowledge Discovery and Data Mining
DOI: 10.1007/978-3-540-71701-0_61
|View full text |Cite
|
Sign up to set email alerts
|

Contrast Set Mining Through Subgroup Discovery Applied to Brain Ischaemina Data

Abstract: Abstract. Contrast set mining aims at finding differences between different groups. This paper shows that a contrast set mining task can be transformed to a subgroup discovery task whose goal is to find descriptions of groups of individuals with unusual distributional characteristics with respect to the given property of interest. The proposed approach to contrast set mining through subgroup discovery was successfully applied to the analysis of records of patients with brain stroke (confirmed by a positive CT … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 7 publications
0
10
0
Order By: Relevance
“…As shown in [7], the subgroup discovery approach to contrast set mining has several advantages. Its application in brain ischemia data analysis has shown that sometimes the right task to address is one-vs-all contrast set mining rather then the classical round robin formulation of contrast set mining.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…As shown in [7], the subgroup discovery approach to contrast set mining has several advantages. Its application in brain ischemia data analysis has shown that sometimes the right task to address is one-vs-all contrast set mining rather then the classical round robin formulation of contrast set mining.…”
Section: Discussionmentioning
confidence: 99%
“…Even though the definitions of subgroup discovery and contrast set mining seem different, the tasks are compatible [7]. From a dataset of class labeled instances (the class label being the property of interest) by means of subgroup discovery [4] we can find contrast sets in a form of short interpretable rules.…”
Section: Round Robin Transformation: Unifying Csm and Sdmentioning
confidence: 99%
See 2 more Smart Citations
“…It is a general approach that has shown to be useful in a variety of application scenarios, like medical consultation systems [ABP06], spatial analysis [KM02], marketing campaign planning [LCGF04], and also in contrast set mining tasks [KLGK07].…”
Section: Introductionmentioning
confidence: 99%